THE EXPERIMENTAL VERIFICATION OF THE EFFICIENCY OF TEACHING TYPING - MADLOVA, Iva (Trends in education, 2013)
The article describes the realized pedagogical experiment, which aim was to verify the efficiency of teaching typing by pupils attending the sixth grade at primary schools. During the research the experimental plan was carried out and included the using of the pretest and the posttest. For getting the research dates the speed test was used that was subsequently statistically evaluated.
Keywords: typing; experiment; speed test